Presenteeism in Nurse Anesthetists: Status and Demographic ‎Correlates from Five Tertiary Hospitals in China - Jiang, Ruxin; Lachica, Toni-An B.; Trajera, Sheilla M.; Ching, Gregory S. (International Journal of Basic and Applied Sciences, 2025)
Presenteeism or working while ill poses risks to clinicians and patients, but remains underexplored among Chinese nurse ‎anesthetists. This cross-sectional, quantitative, correlational study assessed the status and correlates of presenteeism ‎among nurse anesthetists across five tertiary university-affiliated hospitals in Henan Province, China. Using stratified ‎random sampling by hospital, 230 eligible participants completed an online survey comprising the 11-item Nurse ‎Presenteeism Questionnaire (NPQ; 0–3 scale) and demographic/work variables. Presenteeism was high overall (NPQ mean ‎‎= 2.04, SD = 0.58; equivalent to attending work 2 to 5 times while ill in the past six months). The highest means were ‎whole-body fatigue/discomfort (2.18), gastrointestinal symptoms (2.16), and chest distress/shortness of breath/palpitations ‎‎(2.13). Group comparisons showed significant associations between presenteeism and age (χ²=19.80, df=3, p<.001; ‎Cramér’s V=0.29), professional level (χ²=17.20, df=4, p=.002; V=0.27), and employment contract type (χ²=12.60, df=2, ‎p=.002; V=0.23), while gender, education, marital status, position, tenure, night-shift frequency, paid sick leave, training, ‎occupational-injury support, and income satisfaction were not significantly related (all p>.05). Findings indicate a ‎common, symptom-spanning pattern of presenteeism in this workforce, with higher levels observed among older, more ‎senior, and non-permanently contracted nurses. To mitigate harmful presenteeism and enhance patient safety, we propose a ‎Theory of Planned Behavior; an informed program targeting attitudes (risk awareness, perceived benefits/costs), subjective ‎norms (managerial and peer expectations), and perceived/actual control (non-penalized sick-leave access, staffing buffers, ‎ergonomic/health supports). Given the cross-sectional, self-report design, all associations should be interpreted as ‎noncausal and potentially influenced by common-method and recall biases‎.